2013
DOI: 10.3344/kjp.2013.26.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Intractable Hemifacial Spasm Treated by Pulsed Radiofrequency Treatment

Abstract: Hemifacial spasm is defined as unilateral, involuntary, irregular twitching of all or parts of the muscles innervated by facial nerves. Here, we present a case of recurrent hemifacial spasm after microvascular decompression (MVD) treated with pulsed radiofrequency (PRF) treatment with good results. A 35-year-old woman suffered from recurrent hemifacial spasm after MVD that was refractory to medical treatment and botulinum toxin injections. We attempted a left facial nerve block twice. Then, we applied PRF at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Cohen et al [ 10 ] reported that PRFT has repeatedly been demonstrated as a safe and effective procedure, even in instances where other treatment modalities have failed. Its use in a variety of conditions demonstrates the attractiveness of PRFT as a less invasive alternative to surgical intervention that may involve significant morbidity [ 11 ]. Microstructure research has indicated that PRF causes axonal changes more obviously in C fibers than that in Aα or Aβ fibers, which is largely manifested within the mitochondria as micro-cytoskeletal edema, leading to an abnormality in ATP metabolism and ion channel and pump function, thereby blocking the pain transfer in relevant nerves [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cohen et al [ 10 ] reported that PRFT has repeatedly been demonstrated as a safe and effective procedure, even in instances where other treatment modalities have failed. Its use in a variety of conditions demonstrates the attractiveness of PRFT as a less invasive alternative to surgical intervention that may involve significant morbidity [ 11 ]. Microstructure research has indicated that PRF causes axonal changes more obviously in C fibers than that in Aα or Aβ fibers, which is largely manifested within the mitochondria as micro-cytoskeletal edema, leading to an abnormality in ATP metabolism and ion channel and pump function, thereby blocking the pain transfer in relevant nerves [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is an invasive procedure that can lead to severe complications and is contraindicated for elderly individuals, patients with severe systemic diseases and patients whose symptoms are not caused by vascular compression. It is therefore not the therapy of first choice in most cases 9 . Botulinum toxin type A (BTX-A) has been used to treat HFS since the 1980s and provides symptom relief and improved quality of life in about 85% to 95% of cases 10 .…”
mentioning
confidence: 99%
“…A recent report showed that fluoroscope-guided facial nerve block and pulsed radiofrequency treatment might be effective for patients with recurrent facial spasm. [ 7 ] Further studies addressing the selection of appropriate prosthetic materials in microvascular decompression are needed, involving multiple centers and long-term observation of patients after initially successful decompression surgeries.…”
Section: Discussionmentioning
confidence: 99%